Probleme deschise de fenomenologia lui Husserl prin prisma integrării sale în modelul ontologic informaţional propus de Mihai Drăgănescu: Problems started by Husserl’s phenomenology in terms of its integration into ontological informational model proposed by Mihai Drăgănescu - Manolescu, Gorun (Swedish Journal of Romanian Studies, 2020)
Abstract: May another reality exist so as to generate our physical world? Both Mihai Drăgănescu and Edmund Husserl said yes. But there is a main difference between those two approaches. So, Romanian scholar Mihai Drăgănescu proposed an ontological model with strong phenomenological character in which information and material principles are at the same level. Instead Husserl proposed an idealist (transcendental) solution. In this respect Drăgănescu’s model seems to be more general and consistent. Also Mihai Drăgănescu says that Husserl’s Phenomenology can be integrated in his model. But for this some problems appeared. Our present work is dedicated to identifying such problems. In subsequent material we will analyze how these problems can be solved.